Parental and Youth Understanding of the Informed Consent Process for Pediatric Endoscopy. Issue 6 (June 2015) - Jubbal, Kevin; Chun, Stanford; Chang, Jeremy; Zhang, Sherry; Terrones, Laura; Huang, Jeannie S.
ABSTRACT: Objectives: Informed consent (IC) is an essential communication between patient/representative and physician that acknowledges patient autonomy; assent is the equivalent process performed between youth and physician. For clinical procedures involving youth, only the IC process between guardian/parent and physician is required to be performed. Nevertheless, experts recommend that youth undergo assent whenever possible. In the present study, we explored both parental and youth understanding of required IC elements in IC discussions before pediatric endoscopy. Methods: Following signing of IC documents on the day of endoscopy at a tertiary care academic medical center, youth and their parents underwent structured interviews to assess comprehension of key elements of the IC process. Results: A total of 88 children and adolescents and their parents were evaluated. Two youth and 12 parents demonstrated comprehensive understanding of key IC elements for pediatric endoscopy. Suboptimal youth understanding was demonstrated for nature of the procedure (25% with adequate understanding) and related risks (17%), and alternatives (14%) to the procedure. Suboptimal parental understanding was demonstrated for procedure alternatives (24%). Youth overall understanding of IC varied by age, whereas parental global understanding of IC varied by physician. Conclusions: Understanding of IC performed for pediatric endoscopy could be improved in both parents and youth. Our findings suggest that interventions targeting parents, youth, and physicians may be helpful. Further study is needed to determine whether our findings are representative of IC understanding at other pediatric endoscopy centers.